Selecting suitable sites for an Antarctic research station: a case for a new Chinese research station. Issue 5 (14th February 2014) - Xiaoping, Pang; Haiyan, Liu; Xi, Zhao
Abstract Site selection for Antarctic research stations is of great importance and is necessary to support Antarctic expeditions. Site selection is affected by both the scientific investigations planned and the expected life of stations following construction. In the site allocation process, an efficient spatial data management system is required to manage various criteria and a robust allocation method is important to handle decision uncertainties. The aim of this study was to build a criteria system and to conduct a site selection process with aid from geographical information systems (GIS) and the fuzzy analytical hierarchy process (FAHP). In considering the natural environment and building conditions, fifteen factors were used as multiple evaluation sub-criteria and grouped into four main criteria: scientific research, environment, logistical support and topography. Comparisons were made between potentially suitable areas and the locations of existing stations and camps to demonstrate fitness-for-use of the allocation results. Finally, the suitability map was applied to identify candidate sites for a new Chinese research station by considering the position of current stations and areas of scientific interest. This model offers a comprehensive methodology for decision-makers in the assessment of potential Antarctic research station sites.